VD_FINDINFO HC / 2011 / 128 vom 28. Dezember 2010 - VD Tribunal cantonal (2010)
EXPULSION DE LOCATAIRE, POUVOIR D'EXAMEN, DEMEURE | 257d CO, 274g al. 1 CO, 274g al. 3 CO, 457 CPC, 23 LPEBL, 25 LPEBL, 405 CPC (CH)